2009
DOI: 10.1073/pnas.0902940106
|View full text |Cite
|
Sign up to set email alerts
|

The oldest modern therian mammal from Europe and its bearing on stem marsupial paleobiogeography

Abstract: We report the discovery of mammalian tribosphenic teeth from the basal Cenomanian of southwestern France that we refer to a new primitive marsupial-like form identified as a basal taxon of Marsupialiformes, a new clade recognized here to include the crown group Marsupialia and primitive stem lineages more closely related to Marsupialia than to Deltatheroida. Arcantiodelphys marchandi gen et sp nov. shares several significant marsupial-like features ( s.l. ) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 27 publications
1
32
0
2
Order By: Relevance
“…It was previously thought that the clade of living Marsupialia originated in the Cretaceous (Novacek 1992), and that some modern lineages (e.g., Didelphidae) represented "living fossils" (Simpson 1980). However, new fossils and comprehensive phylogenetic analyses of the relevant fossil forms (Rougier et al 1998;Luo et al 2003;Sánchez-Villagra et al 2007;H o r o v i t ze ta l .2009; Vullo et al 2009; but see Beck 2012) have shown that the Cretaceous forms are stemmetatherians and that crown marsupials are exclusively from the Cenozoic. In other words, stem metatherians have a long history within the Mesozoic.…”
Section: Time Of Divergence and Diversity Patterns In Geological Timementioning
confidence: 99%
“…It was previously thought that the clade of living Marsupialia originated in the Cretaceous (Novacek 1992), and that some modern lineages (e.g., Didelphidae) represented "living fossils" (Simpson 1980). However, new fossils and comprehensive phylogenetic analyses of the relevant fossil forms (Rougier et al 1998;Luo et al 2003;Sánchez-Villagra et al 2007;H o r o v i t ze ta l .2009; Vullo et al 2009; but see Beck 2012) have shown that the Cretaceous forms are stemmetatherians and that crown marsupials are exclusively from the Cenozoic. In other words, stem metatherians have a long history within the Mesozoic.…”
Section: Time Of Divergence and Diversity Patterns In Geological Timementioning
confidence: 99%
“…Fossil relatives of marsupials are common in Cretaceous through Miocene localities in both North America and Eurasia [1], [2]. Metatheria includes the common ancestor of all extant marsupials plus all extinct mammals that are more closely related to living marsupials than to extant placentals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cretaceous marsupial fossils are also known from Europe [172,173] and North America [174 -178]. The consensus is that metatherians originated in Asia, and subsequently dispersed to North America and Europe [173].…”
Section: Marsupial Biogeographymentioning
confidence: 99%